The challenges of using video conferencing in educational supervision in the Sultanate of Oman: educational supervisors’ perspectives - تحديات استخدام مؤتمرات الفيديو في الإشراف التربوي من وجهة نظر المشرفين التربويين بسلطنة عمان - Al-Nadabi, Mohammed Hamed; Sahrir, Muhammad Sabri (2020)
This paper aims to discuss the difficulties of using videoconferencing technology in supervisory practices, from an educational supervisory perspective. Whereas, although video conferencing technology is important; The number of educational supervisors who use it is not commensurate with its value and significance, as studies have reported on this technology, perhaps as a new technology. Therefore, the study aimed: to discuss the technical challenges, and the human challenges facing the use of videoconferencing technology in supervision. The researcher used the descriptive and analytical method, whereby a questionnaire was designed consisting of two axes: The first for technical difficulties consists of (11) phrases, and the second for human difficulties consists of (9) phrases. It was applied to a sample of (322) educational supervisors. The study found the following results: The existence of material obstacles that came to a large extent about the use of videoconferencing technology in supervisory operations, as the weakness of the Internet in some remote areas came in first place with the highest arithmetic average of (4.19), followed by “weak infrastructure of schools and directorates. Educational governorates "with an average of (4.08). Followed by the presence of human obstacles that came with a moderate degree regarding the use of video conferencing technology in supervisory operations. Lack of training in employing videoconferencing technology" came in first place with the highest arithmetic average of (3.96). The study includes a set of recommendations, including preparing an integrated guide to explain the mechanism of activating video conferencing in supervisory work. It includes analyzing and studying the psychological, technical and material factors facing the activation of video conferencing.